A review: antimicrobial properties of several medicinal plants widely used in Traditional Chinese Medicine. (4th September 2021) - Chen, Kun; Wu, Wei; Hou, Xiudan; Yang, Qingli; Li, Zhaojie
Abstract: Due to the dramatic increase in the use of antibiotics and growing health threat of bacterial resistance to many commonly used antibiotics, many studies have been directed at developing new and effective antibacterial compounds, among which many new, natural, and effective antibacterial compounds discovered from medicinal plants have drawn great interest and raised new hope for treating the challenges of antibiotic resistance. This review aimed to summarize the most important and widely used medicinal plants that were reported to have antibacterial activities. A general literature search from 2010 to 2020 was conducted using different databases, including Science Direct, Web of Science, and PubMed. According to the literature, three medicinal plants with outstanding antibacterial activities, Taraxacum officinale, Coptis Rhizome, and Scutellaria baicalensis, were screened and reviewed by prioritization. The extraction methods, antibacterial activities of different parts of plants or the plant-derived compounds, spectra of antibacterial activities, and toxicity were described, respectively. However, the antibacterial activities of the extracts or pure compounds as reported in the reviewed literature were mostly based on in vitro assays, and moreover, the deeper antibacterial mechanisms have not been elucidated clearly. Therefore, further studies are required in the fields of purification and identification of the antibacterial compounds, its mechanisms of action, and synergistic effects in combination with other antibacterial drugs, which may be helpful in the development of new antibacterial drugs.